UNTIL SUMMER COMES AROUND - Rolfe, Glenn (London, UK : FLAME TREE PRESS, 2020)
"When fifteen year old Rocky Zukas meets a mysterious dark-haired girl named November, his world is forever changed. The young couple falls under the spell of summer love, but not everyone approves. November's brother, Gabriel, is the keeper of the family's secret, and big brother is always watching, growing more sinister as his bloodlust gets the best of him. Directing his attention to Rocky's family, Gabriel aims to make sure little sister knows who is in charge.
Keywords: Vampires -- Fiction; Old Orchard Beach (Me) -- Fiction; Maine -- Fiction; Vampire fiction; Paranormal fiction